Agama dan Ego Orang Tua (Telaah Kritis atas Spontanitas Anak dalam Pendidikan Keluarga) - Fatkhurahman, M. (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
Parents who believe in providing freedom and unauthorized to children tend to have creative children. Children will naturally develop the confidence to dare to do something originally. Understanding of this issue in greater detailis essential and it is relevance to be studied in depth in this article as currently there had beenvariouscases thatchildren becamethe victims of religious ego of their parents who unilaterally wanted to make them persons whom they wanted. This way is simply not true and too excessive because the mental and character developmentof children will be hampered. Characters or spontaneity that awakened in children will be dropped as the process and habituation done by parents are not elegant. Therefore, the education of children in the family should be returned on its track which leads them to be individualswithgood characters and have freedom based on their own interests, needs, physical and psychological development that are relevant to the values espoused in the surrounding environment.Â Ø¥Ù Ø§ÙÙØ§ÙØ¯ÙÙ Ø§ÙØ°ÙÙ Ø£Ø¹Ø·ÙØ§ Ø§ÙØØ±ÙÙØ© ÙØ£Ø¨ÙØ§Ø¦ÙÙØ§ ÙØºÙØ± ÙØ³ØªØ¨Ø¯Ø§Ù Ø³ÙÙÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙØ¨ØªØ¯Ø¹ÙÙØÂ  ÙØ³ÙÙÙÙÙÙ â Ø·Ø¨ÙØ¹ÙÙØ§-Â  ÙÙÙÙÙÙ ÙÙØ«ÙØ© Ø¨Ø£ÙÙØ³ÙÙ ÙÙ Ø§ÙÙÙØ§Ù Ø¨Ø§ÙØ£Ø¹ÙØ§Ù Ø§ÙØ£ØµÙÙØ©. Ø¥Ù ÙØ«Ù ÙØ°Ø§ Ø§ÙÙÙÙ ÙÙ ØªÙØ§Ø³Ø¨Ù ÙÙ Ø£Ù ÙÙØ¯Ø±ÙØ³ ÙÙ ÙØ°Ø§ Ø§ÙÙÙØ§ÙØ ØÙÙ ÙÙØ¬Ø¯ ÙÙ ÙØ§ÙØ¹ Ø§ÙØÙØ§Ø© ÙÙÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙÙØ¶ÙØ¹ Ø§ÙØ£ÙØ§ÙÙÙØ© Ø§ÙØ¯ÙÙÙØ© ÙÙ Ø§ÙÙØ§ÙØ¯ÙÙ ØÙÙ Ø£Ø±Ø§Ø¯Ø§ ÙÙ Ø¬Ø§ÙØ¨ ÙØ§ØØ¯ Ø£Ù ÙÙÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙÙØ§ ÙØ±ÙØ¯ÙÙØ§.Â  ÙØ°Ø§ Ø§ÙØ£Ø³ÙÙØ¨ ÙÙØ³ ÙÙØ· Ø£Ø³ÙÙØ¨Ø§ Ø®Ø§Ø·Ø¦Ø§ Ø¨Ù ÙÙØ±Ø·Ø§Ø ÙØ£ÙÙ ÙØ°Ø§ Ø§ÙØ£Ø³ÙÙØ¨ Ø³ÙØ¹ÙÙ ÙÙÙÙ Ø´Ø®ØµÙÙØ§ØªÙÙ. ÙØ³ØªÙØ¨Ø· ÙØ°Ù Ø§ÙØ´Ø®ØµÙÙØ§Øª ÙØ£Ù Ø§ÙØªØ¹ÙÙØ¯ Ø§ÙØ°Ù ÙØ§Ù Ø¨Ù Ø§ÙÙØ§ÙØ¯Ø§Ù ÙÙØ³ Ø¬ÙÙØ¯Ø§. Ø¨ÙØ°Ø§ ÙÙØ¨ØºÙ Ø£Ù ØªÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙÙ Ø§ÙØ£Ø³Ø±Ø© Ø¹Ù Ø·Ø±ÙÙ ØªÙØ¬ÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙØ£Ù ÙÙÙÙÙØ§ Ø£ÙÙØ§Ø¯Ø§ Ø°ÙÙ Ø´Ø®ØµÙØ§Øª ÙØØ±ÙÙØ§Øª ØªÙØ§Ø³Ø¨ Ø§Ø³ØªØ¹Ø¯Ø§Ø¯Ø§ØªÙÙØ ÙÙÙÙÙÙÙØ ÙØ±ØºØ¨Ø§ØªÙÙØ ÙØØ§Ø¬Ø§ØªÙÙØ ÙÙÙÙÙÙÙ Ø§ÙØ¬Ø³ÙÙ ÙØ§ÙÙÙØ³ÙØ Ø§ÙÙÙØ§Ø³Ø¨Ø© Ø¨Ø§ÙÙÙÙ Ø§ÙÙÙØªÙØ¨Ø¹Ø© ÙÙ Ø¨ÙØ¦ØªÙÙ.Â